Teaching Origins in High School Science - Westerink, Jack (My University, 1989)
Teaching science involves more than teaching facts, concepts, principles and theories. Science educators also have a professional obligation to expose students to the values associated with those theories. People make decisions on value-laden, scientific questions from the perspective of their own world view. There should be room in our science curriculum to allow the student to form a personal position on the issues of our day after a fair presentation of the full range of alternatives. Even though the student may already have a firm position on the issue in question, the exercise will foster an understanding of the views of others and promote tolerance for those who differ. One of these issues is that of the origin of life.
The objective of this project is to develop a rationale for teaching the full range of alternatives in the science classroom, and to provide a curriculum unit as a resource for teachers who want to give a balanced treatment of the issue in question.
Keywords: teaching; high school; science; educator